ADSORPTION OF HEAVY METALS AND RESIDUAL OIL FROM PALM OIL MILL EFFLUENT USING NOVEL ADSORBENT OF ALGINATE AND MANGROVE COMPOSITE BEADS COATED BY CHITOSAN IN A PACKED BED COLUMN - Rana Jaafar Jawad; Mohd Halim Shah Ismail; Shamsul Izhar siajam (International Islamic University Malaysia Engineering Journal, 2018)
In this study, a novel adsorbent was prepared, namely alginate and mangrove composite beads coated with chitosan (AMCBCC), and performed well to remove heavy metals and residual oil from palm oil mill effluent (POME) using continuous adsorption studies in a fixed bed column under different bed heights. Thomas and Yoonâ€“Nelson models were applied to predict the breakthrough curve and to compute the characteristic parameters such as maximum capacity and the time required for 50% of adsorbate breakthrough. It was found that the total removal percentage of iron ions, zinc ions, and residual oil were 26.75%, 76.74%, and 83% respectively at pH 3, and a bed height 27 cm. Both models can well describe the breakthrough curve of heavy metals and residual oil. These results indicated that AMCBCC can be used to remove heavy metals and residual oil from industrial wastewater. ABSTRAK: Kajian ini menyediakan tentang penjerap baharu iaitu alginat dan manik komposit bakau bersalut kitosan (AMCBCC), berfungsi menyingkirkan logam berat dan sisa minyak daripada efluen kilang minyak sawit (POME) dengan sempurna, menggunakan kajian penjerapan berterusan dalam lapisan lajur tetap pada ketinggian berbeza. Model Thomas dan Yoon-Nelson telah digunakan bagi meramal lengkungan terbaik dan mengira parameter cirian seperti keupayaan maksimum dan tempoh diperlukan bagi 50% lengkungan terbaik penjerap. Jumlah peratusan penyingkiran ion besi, ion zink, dan sisa minyak masing-masing sebanyak 26.75%, 76.74%, danÂ  83% pada pH 3, dan pada ketinggian lapisan 27 cm. Kedua-dua model mampu menggambarkan lengkungan terbaik bagi logam berat dan sisa minyak dengan sempurna. Dapatan ini menunjukkan AMCBCC sesuai digunakan bagi menyingkirkan logam berat dan sisa minyak daripada air sisa industri.